Oral lactate intensifies insulin toxicity during severe insulin-induced hypoglycemia in mice (Brazilian Journal of Pharmaceutical Sciences, 2018)
We investigated whether oral lactate could prevent seizures and deaths in mice with severe hypoglycemia induced by a high dose of insulin. For this purpose, mice were fasted for 15 h and then given an intraperitoneal injection of regular insulin (5.0 U/kg or 10.0 U/kg). Immediately after insulin injection, the mice received an oral dose of saline (control), glucose (5.5 mmol/kg), or lactate (18.0 mmol/kg). Glucose and lactate levels were measured in the blood and brain before and after the seizures began. Glucose and lactate delayed (p < 0.05) the onset of seizures associated with severe insulin-induced hypoglycemia. Elevated (p < 0.05) brain levels of lactate were associated with an absence of seizures in mice that received glucose or lactate, suggesting that lactate could prevent convulsions associated with severe insulin-induced hypoglycemia. However, the same oral dose of lactate that delayed the onset of convulsions also increased the mortality rate. In contrast, diazepam (3.0 mg/kg) prevented seizures and markedly decreased the frequency of death during severe insulin-induced hypoglycemia. The results demonstrated that in contrast to oral glucose, oral lactate intensifies insulin toxicity.